2018
DOI: 10.1186/s12891-018-2120-9
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal outcomes after closed reduction and internal fixation of displaced femoral neck fractures in middle-aged patients: is internal fixation adequate in this age group?

Abstract: BackgroundThere have been many studies regarding nongeriatric femoral neck fractures (FNFs), which included patients of a wide age range (between 20 and 60 years old). We aimed to determine whether internal fixation provided acceptable outcomes for middle-aged patients with displaced FNFs, and identify predictors of successful internal fixation.MethodsA total of 117 patients, aged 50–60 years and who underwent closed reduction and unilateral internal fixation using cannulated screws, were included. The outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…Data on Garden classification were available for the systematic analysis from 14 studies [1620, 2224, 2630, 32]. The fixed effect model was chosen due to nonsignificant heterogeneity in intra-study comparisons ( I 2 = 1%, P = 0.44).…”
Section: Resultsmentioning
confidence: 99%
“…Data on Garden classification were available for the systematic analysis from 14 studies [1620, 2224, 2630, 32]. The fixed effect model was chosen due to nonsignificant heterogeneity in intra-study comparisons ( I 2 = 1%, P = 0.44).…”
Section: Resultsmentioning
confidence: 99%
“…A study reported 47.8% failure rate in 50-to 60-year-old patients. 6 Another study reported higher failure rate in 40-60 years old group compared to < 40 years group. 10 Relative osteopenia in this group was concerned.…”
Section: Discussionmentioning
confidence: 95%
“…In younger patients, the primary treatment for a displaced FNF is internal fixation, which includes multiple cannulated screws fixation, sliding hip screws, and muscle-pedicle bone grafting (MPBG) augmented fixation. [1][2][3][4][5][6] In contrast, hemiarthroplasty or total hip arthroplasty (THA) is the standard treatment for patients >60 years old with a displaced FNF. 1,[7][8][9] However, there is a risk of loss of reduction, non-union, and osteonecrosis of the femoral head (ONFH) in osteosynthesis of a displaced FNF.…”
Section: Introductionmentioning
confidence: 99%
“…The age at which patients cease to be "young" is usually suggested to be 60-70 years, but is still debated. One study from the Norwegian Hip Fracture Register (NHFR) reported a high failure rate of 27% after internal fixation for displaced FNFs in patients aged 55-70 (56), and one recent study from Taiwan reported 84.1% complications in displaced FNFs in patients aged [50][51][52][53][54][55][56][57][58][59][60] years (57), suggesting that more patients should receive an arthroplasty.…”
Section: Displaced Femoral Neck Fracturesmentioning
confidence: 99%